Methane Seep in Shallow-Water Permeable Sediment Harbors High Diversity of Anaerobic Methanotrophic Communities, Elba, Italy - Ruff, S. Emil; Kuhfuss, Hanna; Wegener, Gunter; Lott, Christian; Ramette, Alban; Wiedling, Johanna; Knittel, Katrin; Weber, Miriam (Frontiers in Microbiology, 2016)
The anaerobic oxidation of methane (AOM) is a key biogeochemical process regulating methane emission from marine sediments into the hydrosphere. AOM is largely mediated by consortia of anaerobic methanotrophic archaea (ANME) and sulfate-reducing bacteria (SRB), and has mainly been investigated in deep-sea sediments. Here we studied methane seepage at four spots located at 12 m water depth in coastal, organic-carbon depleted permeable sands off the Island of Elba (Italy). We combined biogeochemical measurements, sequencing-based community analyses and in situ hybridization to investigate the microbial communities of this environment. Increased alkalinity, formation of free sulfide and nearly stoichiometric methane oxidation and sulfate reduction rates up to 200 nmol g-1 day-1 indicated the predominance of sulfate-coupled AOM. With up to 40 cm thickness the zones of AOM activity were unusually large and occurred in deeper sediment horizons (20–50 cm below seafloor) as compared to diffusion-dominated deep-sea seeps, which is likely caused by advective flow of pore water due to the shallow water depth and permeability of the sands. Hydrodynamic forces also may be responsible for the substantial phylogenetic and unprecedented morphological diversity of AOM consortia inhabiting these sands, including the clades ANME-1a/b, ANME-2a/b/c, ANME-3 and their partner bacteria SEEP-SRB1a and SEEP-SRB2. High microbial dispersal, the availability of diverse energy sources and high habitat heterogeneity might explain that the emission spots shared few microbial taxa, despite their physical proximity. Although the biogeochemistry of this shallow methane seep was very different to that of deep-sea seeps, their key functional taxa were very closely related, which supports the global dispersal of key taxa and underlines strong selection by methane as the predominant energy source. Mesophilic, methane-fueled ecosystems in shallow-water permeable sediments may comprise distinct microbial habitats due to their unique biogeochemical and physical characteristics. To link AOM phylotypes with seep habitats and to enable future meta-analyses we thus propose that seep environment ontology needs to be further specified.